500x art in public - Uffelen, Chris van (Braun Pub Ag, 2012)
Works of art make a substantial contribution to cultural identification. When they are placed in a public place, this function is enhanced. However the artwork also acknowledges other tasks: it figuratively announces content in the traditional role, standing as the image of a ruler or at least serves as decoration.